PERANAN PEMUNGUTAN PAJAK AIR PERMUKAAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI BAPENDA II SOREANG - Rahma Deviana Wiangga; Euis Hernawati (JEBS (Journal of Economic and Business Student), 2023)
This study aims to determine how the role of surface tax collection in Bapenda II Soreang. The method used in this reseatch is descriptive qualitative with field data collection, literature study and website, the sample used in this study is data on local revenue revenue in 2017-2021. Local revenue in 2017-2021 fluctuates, the results of the study show that the voting process is good but there are obstacles experienced, namely the lack of knowledge of taxpayers on the prpcess of paying surface taxes, companies that are in arrears and weak supervision. As for the efforts made to overcome these obstacles, namely by following the development of social media, imposting fnes on arrears and increasingg supervision.